2017
DOI: 10.1016/j.jnucmat.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model for long-term nuclear waste glass dissolution integrating chemical affinity and interfacial diffusion barrier

Abstract: Abstract:Understanding the alteration of nuclear waste glass in geological repository conditions is critical element of the analysis of repository retention function. Experimental observations of glass alterations provide a general agreement on the following regimes: inter-diffusion, hydrolysis process, rate drop, residual rate and, under very particular conditions, resumption of alteration. Of these, the mechanisms controlling the rate drop and the residual rate remain a subject of dispute. This paper offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…The new isotope tracer experiments revealed several observations that are not consistent with the classical SAL formation concept. 1,[20][21][22][23][24][25] In particular, the formation of several individual layers with largely different porosity inside a single SAL (exp. QBG-90/150) is difficult to explain by a leaching model that considers (i) the SAL as a residual and restructured glass and (ii) its porosity as a reflection of the free space created by the selective removal of certain network formers and modifiers from the glass, 26 and (iii) a transitional zone presented as hydrated glass 2 ahead of the SAL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The new isotope tracer experiments revealed several observations that are not consistent with the classical SAL formation concept. 1,[20][21][22][23][24][25] In particular, the formation of several individual layers with largely different porosity inside a single SAL (exp. QBG-90/150) is difficult to explain by a leaching model that considers (i) the SAL as a residual and restructured glass and (ii) its porosity as a reflection of the free space created by the selective removal of certain network formers and modifiers from the glass, 26 and (iii) a transitional zone presented as hydrated glass 2 ahead of the SAL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although the count rates were low due to low B concentrations, the 10 B/ 11 B values in the SAL are typically on average higher than the natural B value in the glass (=0. 25), showing that some B from solution is incorporated in the SAL. Similar to B, Ca also depicts complex and unexpected profiles throughout the SAL.…”
Section: Element and Isotope Distribution In The Salmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that a strong acid attack was dependent on the composition of the glass [13]. Ma et al presented a model for the glass dissolution, based on the combination of the chemical affinity and diffusion [35]. Bashir et al studied the kinetics of the dissolution of E-glass fibres in hot alkaline solutions using zero-order and shrinking cylinder models [23,36].…”
Section: Introductionmentioning
confidence: 99%